Nursing Students’ POV toward the English Camp Program at Kampung Inggris Pare to Improve English Skills - Yuyun Putri Mandasari; Eka Wulandari (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
To achieve the vision of globalized graduates, Poltekkes Kemenkes Malang has a strategy to prepare the students to be more skillful in English communication. The strategy is to encourage the nursing students of the International Class to join the English Camp Program in Pare, Kediri, East Java. This study aimed to discover their perceptions regarding the results of the English Camp Program. 38 students of the Nursing International Class who were selected to be the respondents of this study, and their perceptions were collected through a questionnaire and interview and then analyzed descriptively. The findings showed that the Nursing students had a positive point of view regarding the English Camp Program to improve their English skills. In conclusion, this program is considered beneficial for students and can be continued as an alternative strategy for enhancing the English competencies of nursing students at Poltekkes Kemenkes Malang